Large-angle antireflection film, front windshield, and heads-up display system
Patent Information
- Application Number
- CN202522591434.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-05
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2035-12-05
AI Technical Summary
这类膜层在可见光波段(380-780nm)的平均反射率约为3%-5%,且入射角超过±30°时反射率急剧上升,导致图像泛白、细节丢失
[0022]与现有技术相比,本实用新型利用磁控溅射技术在基材上沉积粘结层、承托层以及多层具备纳米级孔隙结构的氧化硅薄膜,有效降低薄膜的折射率。同时结合光学仿真设计,匹配不同膜层结构,最终实现在大角度入射条件下仍保持低折射率特性的目标,所得大角度减反射膜在380-780nm波段内对入射角55°-65°的可见光的反射率小于1%。
Smart Images

Figure CN224851395U_ABST
Abstract
Description
Technical Field
[0001] This utility model belongs to the field of AR antireflective film technology, specifically relating to a large-angle antireflective film, a windshield, and a head-up display system. Background Technology
[0002] Anti-reflection coatings (AR films) are a cornerstone technology in modern optics. Their core principle is to utilize optical interference effects to eliminate reflection losses on the surfaces of optical components (such as glass, resin lenses, and display panels). With the rapid development of consumer electronics, automotive displays, and high-end optical instruments, the performance requirements for AR films are becoming increasingly stringent. They not only require extremely low average reflectivity in the visible light band (380-780nm), but also wide-angle characteristics, high durability, excellent fingerprint resistance, and the potential for application on flexible substrates. Among these, anti-reflection films maintain low reflectivity even under large-angle incident light, meaning they can perform excellently in more demanding and realistic optical environments, bringing numerous benefits.
[0003] For example, augmented reality head-up display (AR-HUD) systems are core display technologies for smart cars and high-end equipment, requiring the maintenance of clarity and contrast of virtual images under complex ambient lighting conditions (such as strong sunlight and interference from oncoming headlights at night). Traditional wet-process antireflective films use a sol-gel process, depositing a film onto a flexible substrate using a chemical solution. Their film structure is often a combination of single or multiple layers of silicon dioxide and aluminum oxide. These films have an average reflectivity of approximately 3%-5% in the visible light band (380-780nm), and the reflectivity increases sharply when the incident angle exceeds ±30°, leading to image whitening and loss of detail. Furthermore, wet-process films have poor weather resistance, easily cracking and peeling under high and low temperature cycling (-40℃ to 85℃) and ultraviolet radiation in automotive environments, with an average lifespan of less than 3 years.
[0004] Existing technologies improve the design of multilayer dielectric film structures, such as using alternating layers of titanium oxide, silicon oxide, and aluminum oxide, and utilize the principle of destructive interference to broaden the effective viewing angle. Specifically, the film system comprises 5-7 dielectric layers, each with a thickness precisely controlled between 10-150 nm, deposited on a PET substrate via vacuum magnetron sputtering. This approach reduces the average reflectivity in the visible light band to below 1.5%, expands the viewing angle to ±50°, and enhances film stability by adding a niobium oxide discharge control layer (0.1-10 nm thick). However, refractive index control relies on changing the target material, resulting in insufficient flexibility. Utility Model Content
[0005] The purpose of this invention is to provide a large-angle anti-reflective film, a windshield, and a head-up display system, wherein the large-angle anti-reflective film can still maintain low refractive index characteristics under large-angle incident conditions.
[0006] To achieve the above objectives, the technical solution provided by a specific embodiment of this utility model is as follows:
[0007] A large-angle anti-reflection film, the large-angle anti-reflection film comprising a substrate layer, a hardening layer, an adhesive layer, a first anti-reflection layer and a second anti-reflection layer stacked sequentially;
[0008] The first antireflective layer is a porous silicon oxide coating with a porosity of 21%-24% and a refractive index of 1.368-1.383;
[0009] The second antireflective layer is a porous silicon oxide coating with a porosity of 71%-74% and a refractive index of 1.126-1.150;
[0010] The large-angle antireflective coating has a reflectivity of less than 1% for visible light with an incident angle of 55°-65° in the 380-780nm wavelength band.
[0011] In one or more embodiments of this utility model, the thickness of the first antireflection layer is 73nm-80nm.
[0012] In one or more embodiments of this utility model, the thickness of the second antireflection layer is 150nm-160nm.
[0013] In one or more embodiments of this utility model, a support layer is provided on the side of the second antireflection layer away from the first antireflection layer. The support layer is a porous silicon oxide coating with a porosity of 29%-32% and a refractive index of 1.329-1.344.
[0014] In one or more embodiments of this utility model, the thickness of the support layer is 12nm-18nm.
[0015] In one or more embodiments of this utility model, the adhesive layer is any one of a silicon plating layer, a nickel-chromium alloy plating layer, a titanium plating layer, and a zirconium oxide plating layer, and the thickness of the adhesive layer is 0.2nm-0.5nm.
[0016] In one or more embodiments of this utility model, a support layer is provided between the adhesive layer and the first antireflective layer, the support layer being a silicon oxide coating with a thickness of 70nm-75nm.
[0017] In one or more embodiments of this utility model, the hardening layer is an acrylic resin layer with a thickness of 2μm-5μm.
[0018] The technical solution provided by another specific embodiment of this utility model is as follows:
[0019] A windshield includes an inner surface and an outer surface disposed opposite to each other, wherein the inner surface is provided with the aforementioned large-angle anti-reflective film.
[0020] The technical solution provided by another specific embodiment of this utility model is as follows:
[0021] A head-up display system includes the aforementioned windshield and a projection light source, wherein the inner surface of the windshield is provided with a head-up display area, and the projection light source is used to emit light toward the head-up display area.
[0022] Compared with existing technologies, this invention utilizes magnetron sputtering technology to deposit an adhesive layer, a support layer, and multiple layers of silicon oxide thin films with nanoscale porous structures on a substrate, effectively reducing the refractive index of the thin film. Simultaneously, by combining optical simulation design and matching different film layer structures, the goal of maintaining low refractive index characteristics even under large-angle incident conditions is achieved. The resulting large-angle antireflective film exhibits a reflectivity of less than 1% for visible light with an incident angle of 55°-65° in the 380-780nm wavelength range. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this utility model or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this utility model. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the structure of a large-angle antireflective film in one embodiment of the present invention;
[0025] Figure 2 This is a schematic diagram of the structure of a support layer for a large-angle antireflective film in one embodiment of the present invention;
[0026] Figure 3 This is a schematic diagram of the structure of a support layer for a large-angle antireflective film in one embodiment of the present invention.
[0027] Explanation of key figure labels:
[0028] 1. Substrate layer; 2. Hardening layer; 3. First antireflective layer; 4. Second antireflective layer; 5. Support layer; 6. Adhesive layer; 7. Supporting layer. Detailed Implementation
[0029] To enable those skilled in the art to better understand the technical solutions in this disclosure, the technical solutions in the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this disclosure.
[0030] The high reflectivity of AR antireflective coatings under large-angle incident light is a challenge that many patented technologies are attempting to overcome. Due to limitations in their design goals or material selection, some existing patents do not achieve ideal reflection suppression effects when dealing with large-angle light. For example, CN218938538U – a monochromatic antireflective coating – uses a magnesium fluoride film of a specific thickness, optimized for blue monochromatic light, and designed for a single wavelength and near-perpendicular incident light. However, large-angle incident light leads to optical thickness mismatch and center wavelength drift, significantly reducing the antireflective effect for that specific wavelength and making it unsuitable for broad-spectrum scenarios. CN104914488B – an antireflective film, optical components, and a method for fabricating optical components – uses hollow silica particles to form a low-refractive-index layer (refractive index 1.22-1.30). While the low-refractive-index layer is beneficial, the film structure is not optimized for large angles (e.g., by using a multi-layered gradient structure), making it difficult to meet the destructive interference conditions at large angles, potentially leading to increased reflectivity over a broad spectrum.
[0031] Another example is CN115343787A-AR film and its preparation method and application, which uses a magnetron sputtering 7-layer interference film system: Al2O3 / Nb2O5 / SiO2 / Nb2O5 / SiO2 / ZrO2, with a total thickness of 300–500 nm. Density is increased through "ion source bombardment + high-temperature preheating," achieving an average reflectivity of 0.4% (400–700 nm). However, the minimum refractive index is still limited by dense SiO2 (1.46). This patent does not introduce any pores; the low-refractive-index layer relies solely on "dense" SiO2, which cannot break through 1.4. Therefore, to achieve R<0.4%, 7 layers must be stacked, doubling the process time and target material cost. The excessive number of layers leads to accumulated stress; with 7 alternations of high / low refractive indexes, the cumulative film thickness tolerance is ±3%, and warpage is >100 µm (0.33 mm glass). This increases the bubble defect rate during subsequent OGS touch bonding. There is no wide-angle performance data; only the reflectivity is given at 0° incident angle. The reflectivity soars to 1.8% at 60°, failing to address the wide-angle needs of applications such as automotive and HUD.
[0032] Conventional antireflective coating manufacturing techniques typically rely on the difference in refractive index between materials (e.g., using Nb₂O₅ with a refractive index of approximately 2.3 and SiO₂ with a refractive index of approximately 1.46) to achieve antireflection. However, this approach is limited by the range of available materials, resulting in a narrow range of achievable refractive index adjustments, which often fails to meet the precise refractive index requirements of different applications. Especially when ultra-low refractive indices (e.g., below 1.3) are required, existing conventional material systems struggle to meet these requirements.
[0033] A specific embodiment of this utility model provides a large-angle anti-reflection film, such as... Figure 1 As shown, it includes a substrate layer 1, a hardening layer 2, an adhesive layer 6, a first antireflective layer 3, and a second antireflective layer 4, which are stacked sequentially.
[0034] Furthermore, the substrate layer 1 is any one of PET, TAC, PC, PEN, PMMA, COP, and glass, with a thickness of 50μm-180μm, specifically 50μm, 80μm, 100μm, 150μm, and 180μm.
[0035] Furthermore, the hardening layer 2 is an acrylic resin layer with a thickness of 2μm-5μm, specifically 2μm, 3μm, or 5μm.
[0036] Specifically, the coating solution used for the acrylic resin layer includes a multifunctional ester reagent, a diluent, and a photoinitiator. The multifunctional ester reagent is one or more of the following: trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol hexaacrylate, dipentaerythritol acrylate, and aliphatic polyurethane hexafunctional (EBECRYL 5129). The diluent is one or more of the following: butanone, methyl isobutyl ketone, acetone or cyclopentanone, propylene glycol methyl ether, ethyl acetate, butyl acetate, amyl acetate, methanol, ethanol, n-propanol, butanol, ethylene glycol ethyl ether, ethylene glycol butyl ether, and diethylene glycol ethyl ether. The photoinitiator is one or more of the following: 1-hydroxycyclohexylbenzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0037] In the specific preparation process, a wet coating method is used to form the hardened layer 2. For example, by weight, 35 parts of aliphatic polyurethane hexafunctional (EBECRYL 5129) are dissolved in a mixed solvent of 30 parts methyl ethyl ketone and 30 parts propylene glycol methyl ether, and finally 5 parts BASF 184 are added to prepare the coating solution. The coating solution is applied to the substrate and baked at 80°C for 2 minutes. The baked sample is then UV cured under UV conditions of 500 mJ / cm². 2 Curing is carried out under ultraviolet light.
[0038] Furthermore, the adhesive layer 6 can be any one of a silicon coating, a nickel-chromium alloy coating, a titanium coating, or a zirconium oxide coating, and the thickness of the adhesive layer 6 is 0.2nm-0.5nm, specifically 0.2nm, 0.3nm, or 0.5nm. By setting the adhesive layer 6, the adhesion of the first antireflective layer 3 can be improved, thereby improving the structural stability of the membrane material.
[0039] Furthermore, the first antireflective layer 3 is a porous silicon oxide coating with a porosity of 21%-24%, a refractive index of 1.368-1.383, and a thickness of 73nm-80nm, specifically 73nm, 75nm, 78nm, or 80nm.
[0040] Furthermore, the second antireflective layer 4 is a porous silicon oxide coating with a porosity of 71%-74%, a refractive index of 1.126-1.150, and a thickness of 150nm-160nm, specifically 150nm, 153nm, 155nm, 158nm, or 160nm.
[0041] Specifically, by adjusting the porosity of the first antireflection layer 3 and the second antireflection layer 4, the refractive index can be controlled and adjusted. At the same time, by combining the optical design of other film layers and matching different film layer structures, the low refractive index characteristics can be maintained even under large angle incident conditions.
[0042] Furthermore, such as Figure 2 As shown, a support layer 5 is provided on the side of the second antireflection layer 4 away from the first antireflection layer 3. The support layer 5 is a porous silicon oxide coating with a porosity of 29%-32%, a refractive index of 1.329-1.344, and a thickness of 12nm-18nm, specifically 12nm, 14nm, 16nm, or 18nm.
[0043] Specifically, the porosity of the support layer 5 is lower than that of the second antireflective layer 4, and the structure is more compact than that of the second antireflective layer 4, which can improve the stability of the membrane structure.
[0044] Furthermore, such as Figure 3 As shown, a support layer 7 is disposed between the adhesive layer 6 and the first antireflective layer 3. The support layer 7 is a silicon oxide coating with a thickness of 70nm-75nm, specifically 70nm, 73nm, or 75nm. The support layer 7 and the support layer 5 are located on both sides of the first antireflective layer 3 and the second antireflective layer 4. Since the first antireflective layer 3 and the second antireflective layer 4 have high porosity and are relatively fragile, the support layer 7 and the support layer 5 can constrain the first antireflective layer 3 and the second antireflective layer 4, suppress deformation, improve structural stability, and enhance the overall stack's resistance to collapse.
[0045] The preparation method of the large-angle antireflective film in this invention is as follows:
[0046] A substrate layer is provided, and a hardening layer is formed by wet coating. Then, an adhesive layer and a support layer are deposited sequentially by magnetron sputtering. The target material used for depositing the adhesive layer is any one of high-purity Si, nickel-chromium, titanium, or zirconium oxide targets, and the atmosphere is argon. The target material used for depositing the support layer is a high-purity Si target, and the atmosphere is a mixture of argon and oxygen.
[0047] Then, a first oxide layer, a second oxide layer, and a third oxide layer are sequentially deposited on the support layer using a magnetron sputtering process (in an atmosphere of argon and oxygen mixed gas). The target material used for depositing the first oxide layer is any one of silicon-aluminum, silicon-copper, and silicon-chromium targets, with a silicon mass ratio of 63%-67%; the target material used for depositing the second oxide layer is any one of silicon-aluminum, silicon-copper, and silicon-chromium targets, with a silicon mass ratio of 16%-18%; and the target material used for depositing the third oxide layer is any one of silicon-aluminum, silicon-copper, and silicon-chromium targets, with a silicon mass ratio of 54%-56%.
[0048] The membrane is then immersed in a phosphoric acid solution (concentration 50%-85%) for etching to remove aluminum, copper or chromium from the first oxide layer, forming the first antireflection layer; aluminum, copper or chromium from the second oxide layer, forming the second antireflection layer; and aluminum, copper or chromium from the third oxide layer, forming the support layer.
[0049] Another specific embodiment of this utility model provides a windshield, which includes an inner surface and an outer surface disposed opposite to each other, and the inner surface is provided with the aforementioned large-angle anti-reflective film.
[0050] Another specific embodiment of this utility model provides a head-up display system, which includes a windshield and a projection light source. The inner surface of the windshield is provided with a head-up display area, and the projection light source is used to emit light to the head-up display area.
[0051] The present invention will be further described in detail below with reference to specific embodiments.
[0052] Example 1
[0053] In this embodiment, the structure of the large-angle antireflective film includes a substrate layer, a hardening layer, an adhesive layer, a support layer, a first antireflective layer, a second antireflective layer, and a support layer stacked sequentially.
[0054] During preparation, a PC substrate with a thickness of 100 μm was selected, and a hardening layer with a refractive index of 1.53 and a thickness of 3 μm was wet-coated.
[0055] A 0.3 nm thick Si binder layer was magnetron sputtered onto the hardened layer. A 73.9 nm thick SiO2 support layer was then magnetron sputtered onto the binder layer.
[0056] A first antireflection layer was magnetron sputtered on the support layer using a silicon-aluminum target: SiAlOx thickness of 75.24 nm and silicon mass ratio of 65.68%. A second antireflection layer was magnetron sputtered on the first antireflection layer using a silicon-aluminum target: SiAlOx thickness of 155.91 nm and silicon mass ratio of 16.64%. A support layer was magnetron sputtered on the second antireflection layer using a silicon-aluminum target: SiAlOx thickness of 15 nm and silicon mass ratio of 55.74%.
[0057] Finally, 60% phosphoric acid was used to etch the alumina in SiAlOx, resulting in a first antireflective layer with a porosity of 22% and a refractive index of 1.374; a second antireflective layer with a porosity of 73% and a refractive index of 1.143; and a support layer with a porosity of 30% and a refractive index of 1.340.
[0058] Example 2
[0059] The preparation method of the large-angle antireflection film in this embodiment is basically the same as that in Example 1, except that the thickness of the hardening layer is 5 μm.
[0060] Example 3
[0061] The preparation method of the large-angle antireflective film in this embodiment is basically the same as that in Embodiment 1, except that the support layer is removed.
[0062] Comparative Example 1
[0063] The preparation method of the large-angle antireflective film in this comparative example is basically the same as that in Example 1, except that the hardening layer is removed.
[0064] Comparative Example 2
[0065] The preparation method of the large-angle antireflective film in this comparative example is basically the same as that in Example 1, except that the adhesive layer is removed.
[0066] Comparative Example 3
[0067] The preparation method of the large-angle antireflective film in this comparative example is basically the same as that in Example 1, except that the thickness of the support layer is 50 nm.
[0068] Comparative Example 4
[0069] The preparation method of the large-angle antireflection film in this comparative example is basically the same as that in Example 1, except that the thickness of the first antireflection layer is 90 nm.
[0070] Comparative Example 5
[0071] The preparation method of the large-angle antireflection film in this comparative example is basically the same as that in Example 1, except that the thickness of the second antireflection layer is 140 nm.
[0072] Comparative Example 6
[0073] The preparation method of the large-angle antireflective film in this comparative example is basically the same as that in Example 1, except that the thickness of the support layer is 20 nm.
[0074] Performance tests were conducted on the large-angle antireflective films in each embodiment and comparative example, and the structures are shown in Table 1.
[0075] Table 1 Performance test results of large-angle antireflective coating
[0076]
[0077] As shown in Table 1, the large-angle antireflective film of this invention achieves low reflectivity at 60° incident angle, with all reflectivities less than 1%, within the designed layer structure and film thickness range. Removing the support layer slightly reduces the structural stability and hardness of the film, but does not affect the transmittance.
[0078] In Comparative Example 1, removing the hardening layer significantly reduced the hardness. In Comparative Example 2, removing the adhesive layer significantly reduced the adhesion. In Comparative Examples 3-6, the thickness of the relevant film layers exceeded the thickness range defined in this invention, resulting in an increase in the reflectivity of the film materials, which did not meet the requirement of low refractive index under large-angle incident conditions.
[0079] In summary, this invention utilizes magnetron sputtering technology to deposit an adhesive layer, a support layer, and a multilayer thin film composed of silicon aluminum oxide, silicon copper oxide, or silicon chromium oxide on a substrate. Subsequently, etching is used to remove the aluminum oxide, copper oxide, and chromium oxide components, thereby forming a silicon oxide thin film with a nanoscale porous structure, effectively reducing the film's refractive index. Furthermore, by combining optical simulation design and matching different film layer structures, the goal of maintaining low refractive index characteristics even under large-angle incident conditions is ultimately achieved.
[0080] It will be apparent to those skilled in the art that this disclosure is not limited to the details of the exemplary embodiments described above, and that this disclosure can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of this disclosure is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this disclosure. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0081] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A large-angle anti-reflective film, characterized in that, The large-angle antireflective film includes a substrate layer, a hardening layer, an adhesive layer, a first antireflective layer, and a second antireflective layer stacked sequentially. The first antireflective layer is a porous silicon oxide coating with a porosity of 21%-24% and a refractive index of 1.368-1.383; The second antireflective layer is a porous silicon oxide coating with a porosity of 71%-74% and a refractive index of 1.126-1.150; The large-angle antireflective coating has a reflectivity of less than 1% for visible light with an incident angle of 55°-65° in the 380-780nm wavelength band.
2. The large-angle antireflective film according to claim 1, characterized in that, The thickness of the first antireflective layer is 73nm-80nm.
3. The large-angle antireflective film according to claim 1, characterized in that, The thickness of the second antireflective layer is 150nm-160nm.
4. The large-angle antireflective film according to claim 1, characterized in that, A support layer is provided on the side of the second antireflection layer opposite to the first antireflection layer. The support layer is a porous silicon oxide coating with a porosity of 29%-32% and a refractive index of 1.329-1.
344.
5. The large-angle antireflective film according to claim 4, characterized in that, The thickness of the support layer is 12nm-18nm.
6. The large-angle antireflective film according to claim 1, characterized in that, The adhesive layer is any one of silicon plating, nickel-chromium alloy plating, titanium plating, and zirconium oxide plating, and the thickness of the adhesive layer is 0.2nm-0.5nm.
7. The large-angle antireflective film according to claim 1, characterized in that, A support layer is provided between the adhesive layer and the first antireflective layer. The support layer is a silicon oxide coating with a thickness of 70nm-75nm.
8. The large-angle antireflective film according to claim 1, characterized in that, The hardening layer is an acrylic resin layer with a thickness of 2μm-5μm.
9. A windshield, characterized in that, The windshield includes an inner surface and an outer surface disposed opposite to each other, and the inner surface is provided with a large-angle anti-reflective film as described in any one of claims 1-8.
10. A head-up display system, characterized in that, The device includes the windshield and projection light source as described in claim 9, wherein the inner surface of the windshield is provided with a head-up display area, and the projection light source is used to emit light toward the head-up display area.
Citation Information
Patent Citations
Anti-reflection film, optical component and method for producing optical component
CN104914488B
AR film and preparation method and application thereof
CN115343787A
Monochromatic light antireflection film
CN218938538U